Դիտարկումներ Համշենի բարբառի հնչյունական առանձնահատկությունների շուրջ - Խաչատրյան, Հասմիկ (ՀՀ ԳԱԱ ԼԻ հրատ.)
In this article, we have examined the phonetic system of the Hamshen dialect, presenting the current state of the speech of the Hamshen Armenians living in Abkhazia. 1. Our observations have led us to the conclusion that the main differences of the two types of the Hamshen dialect distinguished by H. Acharyan do not exist today. Over time, perhaps, these speech types have mixed together, and one can say that, despite very minor differences, the Armenians living in Abkhazia today use mainly one common speech. 2. According to H. Acharyan's classification of the Hamshen dialect consonant system, there are voiced aspirates in the dialect. However, our observations show that today none of the Hamshen dialect speeches has preserved the voiced aspirates evidenced by him. Everyone speaks almost a single common dialect, in which voiced aspirates are absent. The consonant system is divided into three rows: With the voced-to-voiceless shift, the voiced ones have become voiceless, and the voiceless ones have become voiced. For example: beran>peron, glorel>kǝldorush, dnel>tǝnush, dzi>tsi, jur>chur, pagh>bagh, ktsel>gǝjush, tapakel>dabgush, tsaghik>dzaghig, chash>jash, etc. 3. One of the noteworthy phonetic changes characteristic of the Hamshen dialect is vowel sound interchange a>o before the nasals m, n (ban>pon, aman>omon, amis>omis, tan>ton, tsamak>tsomak, anali>onli, etc.). 4. Among the phonetic changes, the most important characteristic of the Hamshen dialect is the presence of the voiceless fricative sound sh before the r followed by the plosives d, t (burd> (pusht, mard>masht, kardal>gashtush, etc.). В данной статье мы рассмотрели фонетическую систему амшенского диалекта, представляя современ-ное состояние говора амшенских армян, проживающих в Абхазии. 1. Наши наблюдения привели нас к тому убеждению, что различий между двумя типами амшенского диалекта, выделенных Г.Ачаряном, ныне не существует. Пожалуй, со временем произошло смешение этих диалектов между собой, и есть основания утверждать, что несмотря на весьма незначительные различия, у армян, живущих сегодня в Абхазии, в основном один общий говор. 2. В системе согласных амшенского диалекта, согласно классификации Г.Ачаряна, присутствуют придыхательные звонкие согласные. Однако наши наблюдения свидетельствуют о том, что сегодня ни в одном из говоров амшенского диалекта не сохранились упомянутые им придыхательные звонкие согласные. Все говорят почти на одном общем диалекте, в котором отсутствуют придыхательные согласные. Система согласных - это трехрядная система: смещением ‹звонкий -глухой› звонкие стали глухими, глухие – звонкими. Например: берáн (рот)>пэрóн, глорел (катать) >кълдоруш днел (положить)>тънуш, дзи (лошадь)>ци, джур (вода)>ч’ур, паг’ (холодный) > баг’, кц’ел (кусать)>гъджуш, тапакéл (жарить)>дабг’уш, ц’аġи́к (цветок)>дзаг’ик, ч’аш (обед)>джаш и т. д: 3. Среди наиболее заметных типичных фонематических изменений в амшенском диалекте-превращение гласной а в о перед носительными звуками м, н (бан>пон, аман > омон, ами́с (месяц) > оми́с, тан (пахта) > тон, анали (пресный) > онли и т. д.). 4. Из фонематических явлений, характерных для амшенского диалекта, важнейшей особенностью также является наличие глухого фрикативного звука ш вместо р’перед взрывными звуками д, тh, ( бур’тh /шерсть/ > пушт, мар’тh /человек/ >машт, кар’тhал /читать/ > гаштуш и т. д.).
Keywords: Բարբառագիտություն